Тайна старинного портрета: [повесть] / К. Врублевская - Врублевская Катерина (Детективы "Искателя", 2004)
Экземпляры: аб (20160216) / Инвентарный номер: 049430 / Цена: 65.00 / Авт.знак: В 84 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6